Employee stock options, EPS dilution, and stock repurchases - Bens, Daniel A.; Nagar, Venky; Skinner, Douglas J.; Wong, M.H.Franco (Journal of Accounting and Economics, 2003)
We investigate whether corporate executives’ stock repurchase decisions are affected by their incentives to manage diluted earning per share (EPS). We find that executives increase the level of their firms’ stock repurchases when: (1) the dilutive effect of outstanding employee stock options (ESOs) on diluted EPS increases, and (2) earnings are below the level required to achieve the desired rate of EPS growth. We also find that executives’ repurchase decisions are not associated with actual ESO exercises, suggesting that they are driven by incentives to manage diluted but not basic EPS, and strengthening our earnings management interpretation.